2015
DOI: 10.1002/pbc.25807
|View full text |Cite
|
Sign up to set email alerts
|

Center-Based Quality Initiative Targets Youth Preparedness for Medical Independence:HEMO-Milestones Toolin a Comprehensive Hemophilia Clinic Setting

Abstract: The HEMO-milestones tool promotes a standardized approach to evaluation of self-management competency. When combined with a collaborative multidisciplinary effort, it increases plans for skill building in patients with hemophilia. This tool is easily modifiable for alternate subspecialty use and does not require extensive training for implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…As adherence is particularly challenged during the transition to self‐care, intensified support is suggested in YWH . It is stressed, however, that education in self‐care should start prior to puberty when patients are more open‐minded . One study showed that while the first steps in self‐management were taken around the age of 12, it took almost ten years with gradual acquirement of more complex skills before complete self‐management was achieved .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As adherence is particularly challenged during the transition to self‐care, intensified support is suggested in YWH . It is stressed, however, that education in self‐care should start prior to puberty when patients are more open‐minded . One study showed that while the first steps in self‐management were taken around the age of 12, it took almost ten years with gradual acquirement of more complex skills before complete self‐management was achieved .…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications recapitulate the recommendations for HCP to deal with the specific challenges for each phase of life with self‐management education of caregivers and patients starting as early as possible . It is noticeable that while parents and HCP often focus on smoothing out cultural differences between paediatric and adult care, YWH emphasize a preference for being well prepared for the shift from family‐centred to individual‐centred care, for example, through joint meetings with paediatric and adult HCP, visits to the adult care clinic, and seeing HCPs alone prior to the final transition …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An efficient dosing program tailored according to patient clinical needs and desires, together with increasing patient empowerment, shared decision making and self-management [44,45], are likely to minimize bleeding events and their complications without uncontrolled increases in healthcare costs. In contrast to 'individualized' prophylaxis [16,17,19,39,46,47], which has already represented an improvement over standard 'one size fits all' dosing, 'patient-centric prophylaxis' integrates patient outcomes and provides the opportunity to flexibly tailor the therapy on an ongoing basis through patient self-management.…”
Section: Innovative Clinical Modelmentioning
confidence: 99%